The input of organic fertilizer can improve soil physicochemical properties and increase cotton yield in southern Xinjiang - Zhao, Yupeng; Bian, Qingyong; Dong, Zhiduo; Rao, Xiaojuan; Wang, Zhiguo; Fu, Yanbo; Chen, Bolang (Frontiers in Plant Science, 2025)
In this study, the improvement effect of different organic substances on compacted cohesive soil in southern Xinjiang was discussed, with emphasis on the influence of different organic substances on soil chemical properties and microorganisms, so as to determine the best carbon source input and provide theoretical support for the rational utilization of organic materials in southern Xinjiang. Field experiments were conducted to evaluate the effects of farm fertilizer, biochar, commercial organic fertilizer, microbial fertilizer and mineral potassium humate on physical and chemical properties of viscous soil, agronomic properties and yield of cotton, with three gradients for each organic fertilizer. The results showed that: (1) all organic fertilizers improved soil structure, among which farm fertilizer significantly reduced soil bulk density and salinity, increased soil organic matter, total nitrogen and available nutrients, and thus increased cotton height, stem diameter and yield. The optimal application amount was 36000 kg/hm². (2) The application of different organic matter increased the contents of organic matter, total nitrogen, hydrolyzed nitrogen, available phosphorus and available potassium in 0-40 cm soil layer, increased the number of bacteria, fungi and actinomyces, and reduced soil salinity; (3) Structural equation model (SEM) was used to investigate the effect mechanism of organic matter input on soil microbial quantity, soil physicochemical properties and cotton yield. The model further confirmed the mechanism: the input of organic matter mainly regulates the number of microorganisms and the richness of microbial species, thereby improving the physical and chemical properties of soil and thereby increasing the cotton yield. The addition of 5 kinds of organic materials can promote the growth and yield of cotton. The comprehensive evaluation shows that the improvement effect is best when the fertilizer dosage is 150% of the recommended amount. In summary, as an effective soil amendment, farm manure can not only alleviate soil compaction, but also significantly improve the growth potential of cotton, which is in line with the goal of sustainable agricultural development.